2018
DOI: 10.5114/jcb.2018.76782
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of Point A and volume-based high-dose-rate plans: a single institution study on adaptive brachytherapy planning for cervical cancer

Abstract: PurposeExternal beam radiation therapy (EBRT) and brachytherapy (BT) with concurrent cisplatin is the standard of care for locally advanced cervical cancer. The applicability of image-guided adaptive volume-based high-dose-rate (HDR) intracavitary brachytherapy planning is an active area of investigation. In this study, we examined whether volume-based HDR-BT (HDRVOL) plans leads to more conformal plans compared to Point A (HDRPointA)-based plans.Material and methodsTwo hundred and forty HDRPointA plans from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Paul et al . reported a relative improvement in organs at risk (OAR) doses per HDR brachytherapy fraction by the volume-based HDR brachytherapy plan compared to the point A-based HDR brachytherapy plan, and described dosimetric advantages of using a volume-based HDR brachytherapy plan to create more conformal plans [16]. Moreover, Lee et al .…”
Section: Purposementioning
confidence: 99%
“…Paul et al . reported a relative improvement in organs at risk (OAR) doses per HDR brachytherapy fraction by the volume-based HDR brachytherapy plan compared to the point A-based HDR brachytherapy plan, and described dosimetric advantages of using a volume-based HDR brachytherapy plan to create more conformal plans [16]. Moreover, Lee et al .…”
Section: Purposementioning
confidence: 99%
“…demonstrated that the dosimetric advantages of volume-based intracavitary planning produced more conformal plans than point-A-based plans. Volume-based plans resulted in a 6-12% reduction in the total dose to 2 cc of the OARs as well as an 8-37% reduction per BT fraction compared to point-A-based plans [ 37 ]. Previous studies have pointed out the strong correlation between local tumor control and D 90 of HR-CTV, with the best results above 85 Gy EQD2 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While IC applicators historically were used with a pre-defined source loading and dose prescription method to specify the dose to points A (Manchester system), in the possession of 3D anatomical information, tailoring the dose to the target volumes became possible with individualized dose optimization [ 20 , 21 ]. Otherwise, this transition cannot be smooth as dose to points A is not suitable for dose prescription when IS needles go through or directly next to the needles, increasing the dose to false value [ 22 ].…”
Section: Purposementioning
confidence: 99%